(untitled) (Bioagro, 2023)
Genetic improvement programs in cacao (Theobroma cacao L) have focused on obtaining new varieties with high yield and resistance to diseases. However, drought tolerance response has not been considered enough in order to face the climate change emergency. Events such as prolonged droughts or excessive rainfall can affect the pollen production of cacao flowers and others reproductive characteristics. Hence, this study was proposed to learn about the hydric deficit influence on pollen production of four Ecuadorian cacao genotypes. The results indicated statistical differences between CCN-51 and the "National" clones (P≤0.05). CCN-51 reached the highest pollen production values in the wettest treatment (26,546 ±100) compared to the “National” clones, which had no differences among them. There was a positive correlation between pollen production and the highest irrigation treatments (r=0.78), observing that while the water level was the highest, the pollen grain formation (PGF) increased, and the opposite when the water level diminished. It is concluded that the adequate water amount in the soil can increase pollen production. However, it is essential to emphasize the strong genetic influence on drought tolerance traits that could be severely affected by climatic changes. The CCN-51 and EET-575 clones should be considered when planning to develop drought-tolerant hybrids of cacao.